DIGLOSIA LANGUAGE IN DRUG SERVICES AT THE PHARMACY ANWAR MEDIKA SIDOARJO HOSPITAL - Suwito (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Communication is a drug service in pharmacy because of its activities as speakers and speech partners because basically communication between speakers and speakers is a sociolinguistic field. The events that occur in language contact carried out by speakers and speech partners at drug services in pharmacies do not occur in a language diglossia. The research objective was to determine the language diglossia in anwar Medika hospital pharmacy. This research uses descriptive qualitative method. Where researchers are placed as the key. Data discussion is done by reducing data, presenting data and drawing a conclusion. The result of the discussion based on Data A is a sentence uttered by a speaker delivered in communicative language that is easy to understand. The answer of a diapotek buyer does not use Indonesian as discussed by the waiter, but speaking in krama alus, generally using Javanese has the best position. Data B, does not use a variety of speeches and interlocutors, because they are the same age in health services to the buyer to convey in smooth, clear and easy to understand language and so that the interlocutor answers in a short language. Data C, a conversation with their servants explained in detail, and was understood. The greeting sentence that is always spoken proves the existence of a person speaking to.